PENGARUH PREFERENSI KERJA DAN PERENCANAAN KARIR TERHADAP KESIAPAN KERJA MAHASISWA ERA DIGITAL DENGAN KESEMPATAN PENGEMABANGAN KARIR - Sari, Gias Gemilang; Achmad, Nur (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the influence of work preferences and career planning on students' work readiness in the digital era 4.0, with career development as a mediating variable. Using a quantitative approach, data were collected through questionnaires from 161 respondents from Muhammadiyah University of Surakarta students. Data analysis was conducted using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4 software. This study focuses on management students facing the digital curriculum-industry gap. The results of the study indicate that job preferences do not directly influence job readiness, but significantly influence career development. Conversely, career planning has a positive and significant influence on both job readiness and career development directly. Key findings demonstrate that career development functions as a partial mediator in bridging the influence of job preferences and career planning on job readiness. This study's theoretical contribution enriches the mediation model of career development on the job readiness of Indonesian Generation Z. Practical implications recommend the integration of digital-based career development programs in higher education to address the demands of a dynamic workplace. This study fills the gap in the synthesis of previously disparate career mediation theories on Indonesian Generation Z. Practical implications recommend digital career workshops and virtual internships in higher education.